Higher Education Changes in Great Britain in XX–XXI centuries - Karužaitė, Daiva (Pedagogika, 2015)
The article reveals development and essential changes of higher education in Great Britain in XX–XXI centuries. During last century Great Britain higher education system has changed dramatically – from elite higher education in the beginning of XX century, which was available for very small part of society, to mass higher education with variety of institutions and education programs. Nowadays there is almost half of Great Britain population (of certain age group) obtaining higher education certificate or diploma. The junction of XX and XXI centuries was signed with significant shift in the gender structure of higher education students: more women obtained fist university degree than men. Ten years later the same was recorded in higher degrees. The intense change of Great Britain higher education from elite to mass inevitably influenced the higher education finance sector. Great Britain used to cover all expenses of higher education from the budget. However, the financial crises occurred in the last decade of XX century, and the government was forced to seek for new financing models of higher education. First time in Great Britain higher education history the tuition fee was introduced. Striving to ensure the higher education accessibility for all social groups in Great Britain, the tuition fees were complemented with the grants and loans with special repayment (or without) conditions. Nevertheless, the financial reform, started in 1998, already was changed several times and has raised lots of critics. Along with the financial reform Great Britain deals with the higher education quality issues. There was no essential discussions about higher education quality in the beginning of the XX century as it was elite higher education. Moving to the mass higher education with variety of institutions and dramatically growing student number, the quality question becomes relevant. Despite the owning the largest number of worldwide level elite universities in Europe, Great Britain seeks to ensure the quality in all higher education institutions in the country. Therefore the Quality Assurance Agency for Higher Education was established. The Agency puts students and the public interest at the center of everything they do. Great Britain higher education quality policy is implemented basing on the Quality Code for Higher Education.